2021
DOI: 10.1021/acs.molpharmaceut.1c00119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excipients on Salt Disproportionation during Dissolution: A Novel Application of In Situ Raman Imaging

Abstract: We have employed a bespoke setup combining confocal Raman microscopy and an ultraviolet–visible (UV–Vis) spectroscopy flow cell to investigate the effect of excipients on the disproportionation kinetics of Pioglitazone HCl (PioHCl) in tablets during dissolution. Three binary formulations of PioHCl, containing citric acid monohydrate (CA), lactose monohydrate (LM), or magnesium stearate (MgSt), respectively, were used as models to study the influence of excipients’ physicochemical properties on the rate of salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This spectral difference can be explained using the protonation of the pyridine ring in PVPy that changes the vibrational modes of the pyridine ring and carbonyl group. 37 However, the peak at 1604 cm −1 was unshifted or shifted to the low wavenumber side in PVPySA−AA and PVPySA−DFA. The reaction between acid and PVPy was insufficient because the acidic constant (pK a ) values of AA and DFA are 4.8 and 1.33, respectively, which is not far from the pK a of pyridine (pK a = 5.25).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This spectral difference can be explained using the protonation of the pyridine ring in PVPy that changes the vibrational modes of the pyridine ring and carbonyl group. 37 However, the peak at 1604 cm −1 was unshifted or shifted to the low wavenumber side in PVPySA−AA and PVPySA−DFA. The reaction between acid and PVPy was insufficient because the acidic constant (pK a ) values of AA and DFA are 4.8 and 1.33, respectively, which is not far from the pK a of pyridine (pK a = 5.25).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Two peaks were observed between 1596 and 1633 cm –1 ; the PVPy base shows a single peak at 1604 cm –1 . This spectral difference can be explained using the protonation of the pyridine ring in PVPy that changes the vibrational modes of the pyridine ring and carbonyl group . However, the peak at 1604 cm –1 was unshifted or shifted to the low wavenumber side in PVPySA–AA and PVPySA–DFA.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Fateixa et al used confocal RS imaging to investigate degradation mechanisms and tablet compositional changes under various storage conditions . Abouselo et al revealed a reliance on salt disproportionation reactions for excipient-influenced microenvironmental pH in situ . Excipients also influence API release, which can be determined by in vitro dissolution profiles.…”
Section: Imaging Dynamic Changes In Drug Formulationsmentioning
confidence: 99%
“…Among the pH-modulation approaches, adding a pH modifier as an excipient is the most common strategy to achieve pH-independent solubility. There are examples of using enteric polymer or carriers to optimize the release further; ,, however, most of the cases have been the addition of small-molecule acids or bases, particularly organic acids (e.g., citric, succinic, tartaric) , or alkalizers (e.g., sodium carbonates, magnesium oxide). ,,, A summary of the physical properties of these frequently used pH modifiers can be found in the literature . The pH modifiers’ effectiveness in controlling microenvironmental pH (pH M ) varies with their acid/base strength (p K a ) and aqueous solubility.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of excipients is of paramount importance because disproportionation often takes place through an excipient-induced solution-mediated mechanism . Among the excipient properties, its acidity/basicity, ,, aqueous solubility, buffering capacity, ,, structural integrity (amorphous/crystalline, particle size/surface area), ,, and hygroscopicity/water activity , are all important parameters. Numerous studies have covered these aspects, including alternative approaches such as using polymer matrices to minimize API/excipient contacts .…”
Section: Introductionmentioning
confidence: 99%